4D recording and analysis: The case study of Nuraghe Oes (Giave, Sardinia). Issue 4 (2015) - Lai, Laura; Sordini, Matteo; Campana, Stefano; Usai, Luisanna; Condò, Francesca
Abstract: The work is related with reality-based 3D modelling and monument analysis. In this project we stressed the importance to use 3D technologies as a tool to improve archaeological research and to increase the production of information from archaeological data to 4D analysis and interpretation. The object of our research is a "nuraghe", a typical megalithic monument built only in Sardinia during the Bronze Age. The building, called Nuraghe Oes, is composed of one main tower and a basement – similar to a bastion – with two smaller towers; it shows peculiar features both in the internal and the external shape and it is well preserved. This project is related with the first season of stratigraphic excavation: after this, we have performed a 3D survey of the entire monument using an integrated approach. We used a TOF laser scanner for a massive data collection of the external and some internal parts of the monument and, overcoming instrument and accessibility limits, we integrated the data using image-based modelling. All datasets have been aligned in a dedicated software in order to produce a complete mesh. After the mesh editing, the model has been textured using HDR images. The high resolution and accuracy of the 3D model allowed us to highlight interesting details in construction techniques and, together with a structural comparison with other nuraghi, to esteem the original height of the main tower. Furthermore, we performed volumetric analysis to esteem the capacity of the stones collapsed inside the main tower for making hypothesis about the ancient/original aspect. Lastly, using information collected during a visual survey of the walls and the 3D analysis, we have been able to map some structural issues of the monument, like cracks or disruptions in the stones and in the masonry. All these analysis are useful to plan further stratigraphic interventions both from time and costing points of view, and to monitor the health of the nuraghe over time.